Survey data on the consequences of COVID-19 and home confinement on the educational community and families in Spain - Guillermo Palau-Salvador (Elsevier, 2021)
This paper presents a dataset concerning the consequences of the COVID-19 pandemic and home confinement on the educational community and families, and the possibilities and opportunities for the return to schools. Data were collected through an online based cross-sectional survey between June 29, 2020 and July 12, 2020 in Spain. A total of 7,305 people who had children in their care during the COVID-19 crisis and the home-confinement period responded to the survey. The survey contained items concerning (i) socio-demographic information, (ii) conciliation of work, personal and family life during confinement, (iii) the impact of the pandemic on the respondent's family, and (iv) the respondents' opinion on their child(ren)'s return to school. Data were analysed using Stata (version 14) and are represented as frequencies and percentages based on responses to the entire survey. Researchers can use the dataset to analyse how home confinement impacted people with children in their care. Additionally, government authorities and education policymakers can use the data to ensure that schools respond to parents' main concerns in a pandemic context, as well as to be prepared to implement appropriate protocols in possible future similar crisis.